Flora of vascular plants of the Seili island and its surroundings (SW Finland) - Brzeg, Andrzej; Szwed, Wojciech; Wojterska, Maria (Biodiversity: Research and Conservation, 2019)
The paper shows the results of floristic investigations of 12 islands and several skerries of the inner part of SW Finnish archipelago, situated within a square of 11.56 km2. The research comprised all vascular plants – growing spontaneously and cultivated, and the results were compared to the present flora of a square 10 × 10 km from the Atlas of Vascular Plants of Finland, in which the studied area is nested. The total flora counted 611 species, among them, 535 growing spontaneously or escapees from cultivation, and 76 exclusively in cultivation. The results showed that the flora of Seili and adjacent islands was almost as rich in species as that recorded in the square 10 × 10 km. This study contributed 74 new species to this square. The hitherto published analyses from this area did not focus on origin (geographic-historical groups), socioecological groups, life forms and on the degree of threat of recorded species. Spontaneous flora of the studied area constituted about 44% of the whole flora of Regio aboënsis. In the studied flora, 22 species threatened in Finland were found.